Electrochemical Characteristics of Cobaltosic Oxide in Organic Electrolyte According to Bode Plots: Double‐Layer Capacitance and Pseudocapacitance. Issue 9 (3rd May 2019) - Xu, Yinsheng; Wang, Shengping; Peng, Huiling; Yang, Zhigao; Martin, Darren J.; Bund, Andreas; Nanjundan, Ashok Kumar; Yamauchi, Yusuke
Abstract: Pseudocapacitive behavior is usually observed in transition‐metal oxide anodes for lithium‐ion batteries, such as Co3 O4 . It is necessary to develop electrochemical technologies for clarifying the properties of the pseudocapacitance in the electrode reactions, as the understanding and controllable application of pseudocapacitance benefits the development of electrode materials with multi‐storage mechanisms for lithium‐ion batteries. To this end, in this work, electrode processes are divided into four component parts with corresponding equivalent circuit diagrams used to emphasize the pseudocapacitive behavior of Co3 O4 . After analyzing the properties of Bode plots in the whole frequency range (10 −2 –10 5 Hz), phase‐angle Bode plots are demonstrated to be suitable for revealing the pseudocapacitance for Co3 O4 at a certain state. In addition, C = 1 / ω Z I m is utilized to determine the magnitude of the pseudocapacitance and double‐layer capacitance. For Co3 O4 in the fully charged state (3 V vs. Li + /Li), the pseudocapacitance and double‐layer capacitance are approximately 180.28 and 1.32 μF cm −2, respectively. Therefore, the goal of monitoring pseudocapacitive behavior for a transition‐metal oxide anode such as Co3 O4 in a certain state without the influence of double‐layer capacitance and faradaic processes controlled by solid‐phase diffusion is realized by using Bode plots, greatly promoting the understanding and controllable application of pseudocapacitance. Abstract : To be so Bode : Phase‐angle Bode plots are demonstrated to be suitable for revealing the pseudocapacitance for Co3 O4 at a certain state, and C = 1 / ω Z I m is utilized to determine the magnitude of the pseudocapacitance and double‐layer capacitance. The goal of monitoring pseudocapacitive behavior for Co3 O4 in a certain state without the influence of double‐layer capacitance and faradaic processes controlled by solid‐phase diffusion is realized by using Bode plots, greatly promoting the understanding and controllable application of pseudocapacitance.